Approaches for the Analysis and Design of Multi-Agent Systems - Villarreal, Pablo David (2002)
This work firstly presents an approach based on the organizational concept of business processes to identify roles and protocols as part of the analysis stage of a methodology for agent-oriented analysis and design. Secondly, the work presents an approach to help to decide when using a mobile agent in a multi-agent architecture is better than using a static one. This approach is based on both the quality attributes specified for the multi-agent architecture and the execution environments of the multi-agent system. A real case is used to exemplify these approaches.